2024
DOI: 10.1186/s40001-024-01747-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evidence of the link between gut microbiome and myalgic encephalomyelitis/chronic fatigue syndrome: a retrospective review

Jing-Hua Wang,
Yujin Choi,
Jin-Seok Lee
et al.

Abstract: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a heterogeneous disorder with elusive causes, but most likely because of clinical and other biological factors. As a vital environmental factor, the gut microbiome is increasingly emphasized in various refractory diseases including ME/CFS. The present study is aimed to enhance our understanding of the relationship between the gut microbiome and ME/CFS through data analysis of various clinical studies. We conducted a literature search in four databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Patients with inflammatory bowel disease often experience depression, which is indicated by various markers of leaky gut such as calprotectin and LBP [41]. There have been studies conducted on MDD and CFS that have found evidence of gut dysbiosis endotypes, which suggest an association with increased gut permeability and pro-inflammatory potential [42][43][44][45][46].…”
Section: The Paracellular Pathway and Long Covidmentioning
confidence: 99%
“…Patients with inflammatory bowel disease often experience depression, which is indicated by various markers of leaky gut such as calprotectin and LBP [41]. There have been studies conducted on MDD and CFS that have found evidence of gut dysbiosis endotypes, which suggest an association with increased gut permeability and pro-inflammatory potential [42][43][44][45][46].…”
Section: The Paracellular Pathway and Long Covidmentioning
confidence: 99%